1994
DOI: 10.1289/ehp.94102s1187
|View full text |Cite
|
Sign up to set email alerts
|

Human milk as a bioindicator for body burden of PCDDs, PCDFs, organochlorine pesticides, and PCBs

Abstract: (HCH) can still be found in human milk. However, the levels ofthese residueshave decreased during the past few years, indicating that the ban is having an effect. A similar trend was found for PCBs. Although their concentration in human milk was at the same level for a long period of time, a slight decrease was observed in the past 2 years. Although the tolerable daily intake concept, which is based on lifetime intake, should not be applied to the relative short nursing period, the results ofhuman milk analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(22 citation statements)
references
References 4 publications
2
19
0
Order By: Relevance
“…To resolve this issue, time-trends should best be followed on country-by-country basis. This has already been done for, e.g., Germany, Norway, The Netherlands, Japan and the USA, and confirms a downward trend (Furst et al 1994; LaKind et al 2001; Liem et al 2000; Papke 1998). This suggests that the possible downward trend in the WHO surveys may indeed be real and no coincidence due to the pooled samples.…”
Section: Discussionsupporting
confidence: 63%
“…To resolve this issue, time-trends should best be followed on country-by-country basis. This has already been done for, e.g., Germany, Norway, The Netherlands, Japan and the USA, and confirms a downward trend (Furst et al 1994; LaKind et al 2001; Liem et al 2000; Papke 1998). This suggests that the possible downward trend in the WHO surveys may indeed be real and no coincidence due to the pooled samples.…”
Section: Discussionsupporting
confidence: 63%
“…These manmade compounds are highly stable and have been used in numerous industrial products, such as diluents, hydraulic fluids, heat transfer fluids, dielectric fluids for capacitors and transformers and many more. Their lipophilic nature and resistance to degradation contribute to their ubiquitous environmental distribution and accumulation in the food chain (Bates et al , 1994); (Fürst et al , 1994). The general population thus is extensively exposed to PCBs through the consumption of contaminated foods, inhalation or skin absorption in work environments (Kogevinas et al , 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The average levels of DDT in BM have varied considerably among nations. After the restriction and the ban of DDT in some nations (in mid-1970s), average BM levels decreased substantially in many (Noren and Meironyte, 2000; Jensen and Slorach, 1991; Fürst et al 1994; Wickstrom et al 1983; Schade and Heinzow, 1998; Chao et al 2006; Shen et al 2007; Jaraczewska et al 2006) but not in all (Kunisue et al 2006; Subramanian et al 2007). Furthermore, several Asian studies (Sudaryanto et al 2006; Kunisue et al 2004a; Kunisue et al 2004b; Minh et al 2004; Sudaryanto et al 2005b; Yu et al 2003) reported accumulated DDT/DDE in BM close to or even higher than the tolerable daily intake guidelines proposed by Health Canada (Van Oostdam et al 1999).…”
Section: Dichlorodiphenyltrichloroethanementioning
confidence: 99%